Drug Offender Treatment in Local Corrections in California and New York, 1991-1993 - Tunis, Sandra ([Verlag nicht ermittelbar], 1998)
The purpose of this multisite program evaluation project was to provide detailed and systematic descriptions of participants and treatment program components for a sample of five drug treatment programs in local jails. Three of the programs were located in California: Jail Education and Treatment (JET), Deciding, Educating, Understanding, Counseling, and Evaluation (DEUCE), and Rebuilding, Educating, Awareness, Counseling, and Hope (REACH). Two programs were in New York State: Substance Abuse Intervention Division (SAID) and New Beginnings. The project was aimed at assessing program completion rates as well as 12-month post-release recidivism for program participants versus matched controls. Background information obtained about the participating offenders includes sex, race, age, education, marital status, and employment status, as well as history of drug use, previous drug treatment, mental illness, inpatient/outpatient episodes, and offenses and sentencing. Additional data cover program location, dates of release from the program and from jail, type of program termination, type of residence upon release, and anticipated post-custody treatment. Information on each conviction/disposition was obtained through state criminal information systems, and state-level criminal history data (rap sheets) were collected for both the treatment and comparison groups. The unit of analysis is arrest events.